1997
DOI: 10.1128/jvi.71.5.3788-3798.1997
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of p53 levels by the E1B 55-kilodalton protein and E4orf6 in adenovirus-infected cells

Abstract: The adenovirus type 5 243R E1A protein induces p53-dependent apoptosis in the absence of the 19-and 55-kDa E1B polypeptides. This effect appears to result from an accumulation of p53 protein and is unrelated to expression of E1B products. We now report that in the presence of the E1B 55-kDa polypeptide, the 289R E1A protein does not induce such p53 accumulation and, in fact, is able to block that induced by E1A 243R. This inhibition also requires the 289R-dependent transactivation of E4orf6 expression. E4orf6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
82
0
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 216 publications
(85 citation statements)
references
References 61 publications
2
82
0
1
Order By: Relevance
“…Although the adenovirus type 5 (Ad5) E4orf6 has been shown to assemble with Cul5, ElonginB, and ElonginC to form an E3 ligase (9, 10) and, together with E1B55K, to induce the degradation of the cellular proteins p53 (11,12,(15)(16)(17)(18)(19)(20)(21) and Mre11 (28), the mechanism by which E4orf6 recruits the Cul5-ElonginB-ElonginC complex remains poorly defined (9,10). By analyzing E4orf6 sequences, we have identified a lentiviral Vif-like BC-box motif (5,29) in human Ad5 E4orf6 (amino acids 131-140).…”
Section: Adenovirus E4orf6 Contains a Vif-like Bc-box Motif That Is Rmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the adenovirus type 5 (Ad5) E4orf6 has been shown to assemble with Cul5, ElonginB, and ElonginC to form an E3 ligase (9, 10) and, together with E1B55K, to induce the degradation of the cellular proteins p53 (11,12,(15)(16)(17)(18)(19)(20)(21) and Mre11 (28), the mechanism by which E4orf6 recruits the Cul5-ElonginB-ElonginC complex remains poorly defined (9,10). By analyzing E4orf6 sequences, we have identified a lentiviral Vif-like BC-box motif (5,29) in human Ad5 E4orf6 (amino acids 131-140).…”
Section: Adenovirus E4orf6 Contains a Vif-like Bc-box Motif That Is Rmentioning
confidence: 99%
“…Adenovirus expresses genes from three different regions of the viral genome to modulate p53 function: the gene products of early region 1A (E1A), the 55 kDa product of the E1B region (E1B55K), and the 34 kDa E4orf6 (10 -14). E4orf6, together with E1B55K, induces the polyubiquitination and degradation of p53 (11,12,(15)(16)(17)(18)(19)(20)(21). Although its ability to induce p53 degradation is correlated with its interaction with Cul5-ElonginB-ElonginC (22), there has been no direct demonstration of the involvement of Cul5 in E4orf6-mediated p53 degradation.…”
mentioning
confidence: 99%
“…These include blockage of p53-mediated transcriptional activation and repression (7,38), interference with suppression of focus formation by p53 (38), inhibition of p53-induced apoptosis, and subcellular redistribution of the tumor suppressor (36). Moreover, E4orf6 interferes with the E1A-E1B-55kDa-induced accumulation of p53 in both lytically infected human and adenovirus-transformed human and rat cells (12,13,36,38,39,45,47,55). This effect is only apparent when E1B-55kDa is coexpressed with E4orf6 and may require complex formation between the two viral proteins (47,55).…”
Section: Vol 74 2000mentioning
confidence: 99%
“…This effect is only apparent when E1B-55kDa is coexpressed with E4orf6 and may require complex formation between the two viral proteins (47,55). E4orf6 and E1B-55kDa most likely target p53 for active degradation through the proteasome, thereby decreasing the half-life and consequently the steady-state levels of the tumor suppressor protein (36,45,55). We recently reported that the ability of E4orf6 to target p53 for degradation resulted in dramatically decreased p53 levels in BRK cells transformed by E1A, E1B, and E4orf6 (ABS cells) compared to cells that only express E1A and E1B (AB cells) (38).…”
Section: Vol 74 2000mentioning
confidence: 99%
“…TP53 gene mutation, frequently observed in patients with HNSCC, has been correlated with radioresistance and shorter survival. [32][33][34] As adenoviral E1B55kDa and E4orf6 proteins have been observed to bind to p53 and induce its degradation, 35 and OSC-19 cells have a nonsense mutation in TP53 gene, 34 the enhanced apoptosis induced by combined OBP-301 and radiation treatment is presumably p53 independent, suggesting that such enhancement can be obtained in TP53-mutated HNSCC cells. As such, the hTERT-promoter element that drives the expression of E1 genes in OBP-301 has potential to exert specific antitumor effects against radiation-resistant HNSCC cells.…”
Section: Discussionmentioning
confidence: 99%